Post-burning regeneration of the Chaco seasonally dry forest: germination response of dominant species to experimental heat shock - Jaureguiberry, Pedro (2015)
Plant species of the Chaco seasonally dry forestof central Argentina have presumably been under a lowevolutionary pressure to develop specialized fire-responsetraits, such as heat-stimulated germination. Nevertheless,other historical factors such as seasonal drought and/orendozoochorus dispersal could have led some species todevelop heat-tolerant seeds. Therefore, heat-tolerant germinationshould be more common than heat-stimulatedor heat-sensitive germination. To test this, we exposedseeds of 26 dominant species from the Chaco region to abroad range of experimental heat treatments and incubatedthem for 30 days at 25 °C and 12 h photoperiod. Wethen scored the percent germination and classified themas heat-stimulated, heat-tolerant or heat-sensitive basedon their germination following heat treatments relative tocontrol. Seventeen species showed heat-tolerant germination,including all native graminoids. Seven species showedheat-stimulated germination, under the less-intense heattreatments. Only two species showed heat-sensitive germination.Endozoochory had no influence on germinationresponses. We suggest that, unlike Mediterranean-climateecosystems, fire was not a major evolutionary force in thedevelopment of Chaco forests, and our results provide greater understanding of the potential response of Chacoplant communities in the face of increasingly frequent fires